Human Resource Management in Sports Judging from the Sports Development Index on Increasing Sports Achievement in Samarinda City - Muhammad Ramli Buhari; Nurjamal Nurjamal; Muchamad Samsul Huda; Didik Cahyono; Jufri Jufri; Ruslan Ruslan (UNIB Press, 2021)
This study aims to determine the management of sports human resources in the city of Samarinda in terms of the Sports Development Index (SDI). The research was conducted in 10 sub-districts in Samarinda City, taking data from 3 institutions as the scope of research, namely the Department of Education, KONI/DISPORA Samarinda, and other Non-Formal Institutions. Research methods use a survey method with a quantitative descriptive approach in terms of SDI. The research instruments used are observation, interview, and analysis of documents. The results of this study indicate; The sports HR Index at the Education Department 0.5009 falls into the middle category, the KONI/DISPORA sports HR Index of 0.2907 in the low category, and the Non-Formal Institution’s sports HR Index 0.0736 is a low category. Overall, the Sports HR Index in 10 sub-districts in Samarinda City of 0.00086 is low.